2001
DOI: 10.1289/ehp.01109s3405
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and blood markers of cardiovascular risk.

Abstract: Recent studies have linked air pollution to tens of thousands of premature cardiovascular deaths per year. The mechanisms of such associations remain unclear. In this study we examine the association between blood markers of cardiovascular risk and air pollution in a national sample of the U.S. population. Air pollution concentrations were merged to subjects in the Third National Health and Nutrition Examination Survey (NHANES III) in the United States, and the association with fibrinogen levels and counts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
151
0
10

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(171 citation statements)
references
References 34 publications
10
151
0
10
Order By: Relevance
“…Vehicular traffic is a major contributor to outdoor air pollution and can produce high levels of fine particulate matter, carbon monoxide, and nitrogen oxides. NO 2 has been associated with plasma fibrinogen [22,23], and also correlated with fine particulate matter, which can provoke alveolar inflammation, which can result in increased coagulability through the release of cytokines [18]. As described elsewhere [5], these mechanisms suggest that air pollution may produce hemodynamic disturbances that could increase the risk of cardiovascular, and by extension, cerebrovascular events.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Vehicular traffic is a major contributor to outdoor air pollution and can produce high levels of fine particulate matter, carbon monoxide, and nitrogen oxides. NO 2 has been associated with plasma fibrinogen [22,23], and also correlated with fine particulate matter, which can provoke alveolar inflammation, which can result in increased coagulability through the release of cytokines [18]. As described elsewhere [5], these mechanisms suggest that air pollution may produce hemodynamic disturbances that could increase the risk of cardiovascular, and by extension, cerebrovascular events.…”
Section: Discussionmentioning
confidence: 89%
“…Others have speculated that increased risks of stroke relate to the ability of air pollution to increase plasma viscosity [19], raise heart rate [20], and alter heart rate variability [21]. Elsewhere, studies have documented associations between plasma fibrinogen and particulate matter and NO 2 , [22,23] and recently, long-term exposure to ambient air pollution was found to promote atherosclerosis in animals [9]. As atherosclerosis is the most common cause of ischemic stroke [24], air pollution may be particularly relevant for this type of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the effect of air pollution on systemic inflammation showed inconsistent results. Some studies found associations for short-term exposure up to several days to elevated particulate air pollution levels and increased levels of inflammatory markers [3,4], whereas other studies found no association of short-term exposure and inflammatory response [5,6] or were limited to prediseased subjects [7]. Long-term exposure to particulate air pollution has been associated with an increased inflammatory response [8][9][10], but others did not find a consistent relationship [11].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported no effects on leukocytes or neutrophils after exposures to concentrated ambient air (Gong et al, 2003), diesel exhaust (Lucking et al, 2008;Mills et al, 2005Mills et al, , 2007, or to concentrated ambient UFP (Gong et al, 2008). By contrast, short-term increases in ambient air PM levels have been associated with increased levels of circulating leukocytes in the general population and patients with chronic pulmonary diseases (Bruske et al, 2010;Schwartz, 2001). Two studies reported a decrease in circulating leukocytes after exposure to ambient air PM (Ruckerl et al, 2007b) or concentrated ambient air particles (Ghio et al, 2003), while a recent study reported a significant increase in neutrophils after long-term exposure to PM 10 , PM 2.5, O 3 and NO 2 (Chuang et al, 2011) . The expression of adhesion markers CD11b and CD62L on monocytes was significantly inversely associated with indoor PNC, endotoxin or fungi levels in our study, suggesting that systemic inflammation responses were affected by the exposure.…”
Section: Discussionmentioning
confidence: 97%